Relation between the incident solar radiation and the duration of bright sunshine at Madras - MOOLEY, D. A.; BEDEKAR , V. C.; RAGHAVAN, S. (MAUSAM, 1962)
From the daily, weekly and monthly values of Q/Q A and n/N the least square regression constants, a and b in the equation, Q/QA = a + b (n/N), have been calculated for Madras, Q and Q A being radiation one square centimetre of horizontal surface at the surface of the earth and at the top of the atmosphere respectively, n and N being the actual and the maximum possible durations of bright sunshine respectively. Daily data have also been grouped season-wise for the dry and the monsoon seasons and the values of a and b have been calculated for the two seasons. Correlation coefficients between Q/Q A and n/N have also been calculated. The values of a and b for Madras have been compared with those obtained by different workers in other of the world. The mean monthly incident radiation at a few placed on the east coast having the same cloud regime as at Madras has also been worked out.